Oraliterature from the south of Tolima as border literature: beyond epistemic coloniality - Guerrero Rivera, Javier; Guzmán Chaves, Juan Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of the research is to analyze the constituent elements of peasant oral literature as “border literature”, decolonial and intercultural potential. The research is developed under the qualitative paradigm (ethnographic tradition). Free conversations are held with men and women from peasant communities in two municipalities in the south of Tolima (Colombia), which yield twenty five stories. The discovery of the characteristics and themes of the stories accounts for their innovative, counter-hegemonic, community and resistance character, revealing an aesthetic and art different from the literary canon. Likewise, they express an active and transforming role of the peasantry, beyond historical discrimination and colonialism. In short, these expressions reflect collective and individual experiences and worldviews, elements of identification and regional memory.